Aplikasi Polyhalite sebagai Pengganti ZK dan Pengaruhnya terhadap Kadar K, Mg, dan S Daun, Produksi, dan Mutu Buah Jeruk Siam - Sutopo Sutopo; Titistyas Gusti Aji (Universitas Sebelas Maret, 2020)
As a natural mineral that contains several macro elements, polyhalite (K2Ca2Mg (SO4) 4H2O) has good potential as a fertilizer. This study aims to study the effect of polyhalite on branch growth, leaf nutrition (K, Mg and S), chlorophyll index, harvest weight, fruit quality, and the effective dose of Siam citrus. A 4-year-old Siam citrus planted on vertisol soil was treated with 6 fertilizer treatments: 625; 1,000; 1,375; 1,750; 2.125 kg polyhalite and 625 kg ZK/hectare/year. The experiment using a randomized block design was repeated 3 times. The results showed thatthe application of polyhalite at the same K2O dose as ZK increased leaf Mg content, chlorophyll index and total juicesolids significantly. Polyhalite application of 1,750 kg/hectare (2.8 kg/tree) is an effective dose for mature Siam citrus in vertisol with moderate K status and high Ca and Mg status.